Practices, advantages and challenges for the construction and maintenance of an agricultural family cooperative (Desenvolvimento em Questão, 2024)
The study aimed to analyze the practices, advantages and challenges faced in the construction and maintenance of an agro-family cooperative. A descriptive research was carried out through a qualitative case study, triangulating interviews with cooperative agents, documents and questionnaires answered by cooperative members. To this end, the content analysis technique was used. Among the main findings, the challenges related to the difficulties in aligning the objectives of cooperative members and the dependence on government programs stand out. Regarding practices, the incentives for organic production and the provision of technical assistance and training to cooperative members stood out. Considering the advantages, the positive impacts are relevant in relation to the direct contact between the member and the consumer, the increase in family income and quality of life, in addition to maintaining families in the countryside. The work brings social benefits to the creation and consolidation of small farmer cooperatives more efficiently and brings important elements to the academic field related to the study of agro-family cooperatives. The work opens up a research opportunity considering that difficulties related to the issue of gender in the countryside were highlighted as well as the maintenance and professionalization of farmers through family agribusines and additional studies related to organic products.
Keywords: Agrofamily Cooperative; Family farming; Cooperative Management